Vaginal microbiota in menopause - Martinus, Martinus; Wibawa, Larisa Paramitha; Effendi, Evita Halim; Yusharyahya, Shannaz Nadia; Nilasari, Hanny; Indriatmi, Wresti (UI Scholars Hub, 2016)
The human vagina together with its resident, microbiota, comprise a dynamic ecosystem. Normal microbiota is dominated by Lactobacillus species, and pathogen microbiota such as Gardnerella species and Bacteroides species can occur due to decrease in Lactobacillus domination. Lactobacillus plays an essential role in keeping normal vaginal microbiota in balance. Vaginal microbiota adapts to pH change and hormonal value. Changes in the vaginal microbiota over a woman’s lifespan will influence the colonization of pathogenic microbes. They include changes in child, puberty, reproductive state, menopause, and postmenopause. Estrogen levels change will affect the colonization of pathogenic microbium, leading to genitourinary syndrome of menopause. Vulvovaginal atrophy is often found in postmenopausal women, and dominated by L. iners, Anaerococcus sp, Peptoniphilus sp, Prevotella sp, and Streptococcus sp. The normal vaginal microbiota’s imbalance in menopause will cause diseases such as bacterial vaginosis, and recurrent vulvovaginal candidiasis due to hormonal therapies. Changes in the vaginal microbiota due to bacterial vaginosis are characterized by decrease in H2O2-producing Lactobacillus. They are also caused by the increase in numbers and concentration of Gardnerella vaginalis, Mycoplasma hominis, and other anaerob species such as Peptostreptococci, Prevotella spp, and Mobiluncus spp.